Communication Accommodation and Identity Gaps as Predictors of Relational Solidarity in Interfaith Family Relationships. (2nd January 2020) - Morgan, Toni; Soliz, Jordan; Minniear, Mackensie; Bergquist, Gretchen
Abstract : Guided by Communication Accommodation Theory (CAT) and Communication Theory of Identity (CTI), the purpose of this study was to investigate how families communicatively negotiate religious differences and how that negotiation is related to parent-child relational solidarity. Specifically, we examined the direct effects of (non)accommodative communication on relational solidarity and indirect effects via identity gaps. Using a cross-sectional survey from emerging adult college students ( N = 234), we found nonaccommodative communication is indirectly related to lower relational solidarity through increased identity gaps. Accommodative communication is indirectly related to higher relational solidarity through decreased identity gaps. When parents use accommodative strategies, they may help alleviate the mismatch between their child's personal, enacted, and relational layers of identity, and foster increased relational solidarity.